Consultations in dermatology studies of orphan and unique patients - Shelley, Walter B. 1917- (Cambridge University Press, 2006)
This is a handbook on dermatologic differential diagnosis and clinical management, focusing on sixty-two challenging and vexing clinical cases that the Shelleys have encountered in over fifty years of patient practice in dermatology. The management problems of these extremely perplexing cases go far beyond evidence-based medicine. Each case is presented as a well-written vignette, told in a case-study tone. The authors first present the background of each case in a concise, thorough, manner including all the important clinical details, including tests and results. The authors then reveal the process involved in the diagnosis and the therapy involved. Finally, they include a section called 'Questions for the Doctor', which suggests relevant questions that the doctor should be pondering in each case. This is the perfect book for residents preparing for their boards.